Diversity and Weed Dominance in Coconut Plantation Area At diferent Crop Stadiums in Tial Village, Central Maluku District - Tanasale, Vilma Laurien; Kilkoda, Abdul Karim; Lahalimu, Zulkarnaen (Departemen Hama dan Penyakit Tumbuhan Fakultas Pertanian Universitas Padjadjaran, 2024)
Weeds are plants whose presence is unwanted because they interfere with and reduce the yield of cultivated plants. One of the plantation crops with high economic value is coconut. Coconut is a commodity that can make a major contribution to the economy in Indonesia. The presence of weeds in coconut plantations will reduce yields. This study aims to determine the diversity and dominance of weed species that grow in the coconut plantation area in Tial Village, Central Maluku Regency. This study uses the